Manajemen Konflik Rumah Tangga dengan Pendapatan Istri Lebih Tinggi Daripada Suami - Fitrah Ash-Shiddiq, R.Muhammad Ikhwanul; Ubaidillah, Ubaidillah; Arif, Muhamad Ridwah; Nurhayati, Alfisyah (CV. ITTC INDONESIA, 2024)
This research aims to find out how household conflict is managed with the wife's income being higher than the husband's. This research uses descriptive qualitative research methods with data collection techniques using interviews and observation. The subjects of this research were 4 married couples. The research results showed that 3 out of 4 subject pairs used collaborating resolution and 1 out of 4 subject pairs used accommodating conflict resolution. This shows that collaborating can make families more harmonious and supportive of each other. Meanwhile, accommodating can have a lasting impact because one party is seriously disadvantaged.